Comparison between the two poets of Islam - Mohd. Shamsuddin, Salahuddin (Advances in Social Sciences Research Journal, 2021)
The great Islamic poets ’Aḥmad Shawqī and Iqbāl both lived in one era and experienced the great events that have passed through the Islamic world, as they both have experienced the bitterness of foreign occupation and the suffering of Western colonialism. Both of them were proud of their religion, jealous of Islam and the Muslims to be attacked by their opponents. They were saddened by their failure to take the causes of strength, pride and glory. It was very painful to them to see the home lands of Muslims were occupied and their affairs were all dysfunctional, and both of them were influenced by the calls for reform and the movements of renewal that were attracted to high societies, the national press and the guiding books. Both of them wanted to extend their poetry and poetic message from the borders of their homeland to the extent of a wide horizon.